Application of Military Lubricants in Commercial Hydraulic/Power Transmission Systems and Components. - Marbach,H W , Jr; Lestz,S J (1983)
The MACI Hydraulic System and Components Program was selected to perform technical evaluation and assessment of commercially available qualified and fielded military specification lubricants and to determine if such oils can be used as hydraulic lubricants in Army commercial Construction Equipment (CCE) and Selected Material Handling Equipment (SMHE). Eight military specification lubricants: one MIL-H-46001C Grade 3, one MIL-L-2104C Grade 10W, one MIL-L-46167 Arctic equivalent to Grade 0W-20 and five MIL-L-46152B Grade 15W-40 were extensively evaluated using eleven selected tests required by manufacturers and one test developed by AFLRL in conjunction with John Deere personnel. From the data developed, the Army lubricants passed 90 percent of all the tests. Also, from the data presented, it appears that the MIL-L-46152B Grade 15W-40, the MIL-L-2104C Grade 30, the majority of the grade 10W, and possibly the MIL-H-46001C Grade 3 and MIL-L-46167 equivalent to Grade 0W-20 (in cold climates) lubricants are good potential candidates for use as hydraulic and power transmission lubricants within the Army CCE/SMHE system.